The effects of carbohydrate mouth rinsing on upper body strength and muscular endurance performance - Karayiğit, Raci; Sari, Cengizhan; Yıldırım, Ulaş Can; Gurkan, Oguz; Eser, Mustafa Can; Kılınç Boz, Hilal; Bayrakdar, Akan (Progress in Nutrition, 2021)
The purpose of this research was to examine the effect of rinsing of carbohydrate in the mouth on bench press strength and endurance performance in resistance-trained athletes. 15 men (Age: 21.6 ± 1,3 years, Height: 181.2 ± 10,0 cm, Body Weight: 83.3 ±14.4 kg), who performed upper-body resistance training at least 5 days a week for the last 1 year, participated in this research. After the familiarization test day, participants took part in a total of 2 test days with a randomized, counterbalanced, crossover study design: 6% (1.5 gr) weight / volume (w/v) carbohydrate mouth rinsing (cho) with 25 ml water or mouth rinse with water (PLA). After a 10-hour night fasting, with olympic barbell bar, one repetition maximum (1RM) of participants was determined to evaluate upper body strength, immediately before 1RM attempt participants rinsed the solution. Muscular endurance was measured by lifting 40% of 1RM until exhaustion in 3 sets. 3 min of passive rest was allowed between sets and at the beginning of each minute mouth rinsing was applied. During the test protocol heart rate (HR), lactate (LA), glucose (GL), arousal (AR) and ratings of perceived exertion (RPE) were measured. Paired Samples T-test and two-way repeated measures ANOVA were used for data analysis. No significant differences were detected between the trials in the values of upper-body strength (p=0.43), muscular endurance (for repetition number, p=0.57; for total kg, p=0.43), HR (p=0.71), LA (p=0.42), GL (p=0.36), AR (p=0.19) and RPE (p=0.51).